SAT0063 Remote Assessment of Daily Fluctuations of Patient-Reported Disease Symptoms and Activity in Rheumatoid Arthritis: Feasibility, Compliance and Acceptability. (15th July 2016) - Gourley, I.; Calderon, C.; Beyer, M.; Hamade, L.; Margolies, R.; Gilmer, K.; Messina, T.; Fields, O.; Tisdale, D.; Curran, M.; Rowe, A.
Abstract : Background: Existing clinical measures for Rheumatoid Arthritis (RA) patients, eg: Disease Activity Score (DAS)28 are labor-intensive and typically compiled once every three months by a physician. In contrast, wearable fitness activity trackers allow for continual measurement of activity and lifestyle events. If correlated to disease activity, use of data from "wearable" will provide an understanding of impact on activity on a more frequent basis than the physician-applied tests. Objectives: The primary aim of this study was to determine feasibility, patient compliance and acceptance using an activity tracker together with a novel smartphone-based electronic Patient Reported Outcome (ePRO) app (Remote Access to RA [RA-RA] app developed in-house) for RA patients. Methods: Smartphone users diagnosed with RA (n=15) were recruited to wear an activity tracker and use the RA-RA app daily for one week. The patients attended two study sessions. During the first session patients were dispensed the activity tracker. The investigator installed the activity tracker companion and the RA-RA apps on the patient's smartphone and provided instructions for their use. Patients wore the activity tracker for one week, and were asked to complete RA symptom questionnaires on a regular basis (eg:morning, evening, and weekly). During the study period, the activity monitor collected objective measures of patient activity while the RA-RA app collected patient reported outcome measures (eg: stiffness, sleep quality, joint pain). Blinded activity and RA symptom data were automatically transferred to and stored on a clinical electronic data capture system. During the second session, patients were interviewed regarding their experiences; likes, dislikes, difficulties, and provided feedback on the RA-RA app, activity tracker and its accompanying app. Patients also described any instances and reasons for non-compliance with using the app or wearing the activity tracker. Results: Thirteen of fifteen patients successfully used the activity tracker and wore it for the duration of the study week.Overall, patients found the RA-RA app easy to use for tracking their RA symptoms and activity. Many patients reported that RA-RA accurately described their RA symptoms. Some patients experienced app errors and required assistance from study staff. Overall, patients liked the on-screen controls. Patients provided valuable feedback on interface design considerations (eg: keypad or the arrows for time entry). Preliminary analysis showed some correlation between duration of morning stiffness reported in the app and level of morning activity captured by the activity tracker. Conclusions: Digital healthcare application, use of the activity tracker, and a smartphone-based ePRO is a feasible, easy to use and acceptable system for the collection of daily fluctuations of symptoms and activity in RA patients. Based on the results of this pilot study, the next trial will be in a clinical setting with RA patients receiving treatment. This study will establish correlation of patient's activity and ePRO information with the standard clinical information (ACR, DAS28, and HAQ), as well as serum and imaging biomarkers to determine disease activity and inflammation. Disclosure of Interest: I. Gourley Employee of: Janssen R & D, LLC, C. Calderon Employee of: Janssen R & D, LLC, M. Beyer Employee of: Janssen R & D, LLC, L. Hamade Employee of: Janssen R & D, LLC, R. Margolies Grant/research support from: Janssen R & D, LLC, K. Gilmer Employee of: Janssen R & D, LLC, T. Messina Employee of: Janssen R & D, LLC, O. Fields Employee of: Janssen R & D, LLC, D. Tisdale Employee of: Janssen R & D, LLC, M. Curran Employee of: Janssen R & D, LLC, A. Rowe Employee of: Janssen R & D, LLC